1982
DOI: 10.1515/jnet.1982.7.5.269
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Dependence of Transport Coefficients of Binary and Ternary Mixtures Through Inactive Membranes

Abstract: An experimental investigation on the electrokinetic transport of ternary and binary mixtures through inactive membranes is described. Pyrex glass and quartz were used to perform the porous membranes. The phenomenological equations between the thermodynamic fluxes and forces were always found to be linear. The geometric parameters of the porous membranes were found to be independent on the composition of the mixture. The concentration dependence of the coefficients L 21 and L 22 in the Pyrex-binary mixture syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The experimental devices and procedures for hydrodynamic permeability, streaming potential and electroosmosis measurements were the same as those described earlier [12][13]. The interruption technique described by Lakshminarayanaiah [1], was followed in the determination of electroosmotic flux.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental devices and procedures for hydrodynamic permeability, streaming potential and electroosmosis measurements were the same as those described earlier [12][13]. The interruption technique described by Lakshminarayanaiah [1], was followed in the determination of electroosmotic flux.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of driving the liquid through the plug with a Mariotte tube, this was done with nitrogen, following a procedure similar to that used for the measurements of streaming potentials. Details of this experimental setup can be found in [1,3].…”
Section: Methodsmentioning
confidence: 99%
“…Several of these papers analyse the dependence of the first order phenomenological coefficients L tj with the composition of the liquid mixture employed ( [1] and references therein). However, papers considering the concentration dependence of the second order coefficients L ijk are very scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are considerable According to De Groot et al (27), the linear phenomenodiscrepancies in the literature on the electrokinetic properties logical equations for sedimentation and electrophoresis are: of those mixtures. Thus, some authors (4-7) have found linear dependences, while other authors (7)(8)(9)(10)(11)(12) obtained…”
Section: Theorymentioning
confidence: 99%